2022
DOI: 10.2105/ajph.2021.306625
|View full text |Cite
|
Sign up to set email alerts
|

Refusal Rates to Sexual Orientation and Gender Identity Items in the Behavioral Risk Factor Surveillance System, 2014–2019

Abstract: Objectives. To explore trends in sexual orientation and gender identity (SOGI) item refusal in the Behavioral Risk Factor Surveillance System (BRFSS). Methods. We used annual data from 7 US states that implemented the SOGI module of the BRFSS from 2014 to 2019 to examine prevalence of sexual orientation (n = 373 332) and gender identity (n = 373 336) item refusal. Analyses included the weighted Wald χ2 test of association between refusal and year and logistic regressions predicting refusal by year. We weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…This is consistent with earlier studies of SOGI refusals in surveys. 18,22 Finally, consistent with the prior literature, our study also found higher nonresponse and indeterminate responses among older adults, defined as 65 years and older. 18,37 Limitations Data on SOGI are included in BRFSS only among those states electing to use the optional module, which precludes certainty in generalizing these findings to the nation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with earlier studies of SOGI refusals in surveys. 18,22 Finally, consistent with the prior literature, our study also found higher nonresponse and indeterminate responses among older adults, defined as 65 years and older. 18,37 Limitations Data on SOGI are included in BRFSS only among those states electing to use the optional module, which precludes certainty in generalizing these findings to the nation.…”
Section: Discussionsupporting
confidence: 91%
“…19,25 Consistent with prior literature, we assessed sex, race/ethnicity, age, employment, marital status, educational attainment, and interview language to determine variation in non/indeterminate responses by these characteristics. 22,26,27…”
Section: Methodsmentioning
confidence: 99%
“…Although no studies have compared SOGI nonresponse rates by race and ethnicity from self-administered surveys, unadjusted results from two studies based on the SOGI module of the Behavioral Risk Factor Surveillance System (BRFSS) survey produced mixed findings. One study, based on seven states, reported that non-Hispanic White adults had the lowest gender identity nonresponse rate, but adults of multiple races or non-Hispanic other race had lower nonresponse rates than White adults for sexual orientation [19]. The other study, based only on Washington BRFSS, found that Hispanic and Asian adults had the highest sexual orientation nonresponse rates, whereas non-Hispanic White adults had the lowest [20].…”
Section: Plos Onementioning
confidence: 99%
“…The purpose of this study was to determine the likelihood of adults to provide their sexual orientation and gender identity during the enrollment process of a digital health application. It also sought to test our hypotheses that SOGI response rates are lower among members in older age groups, members who reside in the southern and central regions of the US, and are not White [11,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%